Experimental Study on Vibration and Noise Characteristics of Steel-Concrete Railway Bridge - Lucjan Janas (Sensors, 2021)
The paper presents the results of vibroacoustic tests of a plate girder railway bridge consisting of two parallel dilated structures and a common ballast trough. The requirements currently set for railway bridges relate to, among others, vibrations considered as one of the criteria for traffic safety and to noise emissions that may pose a threat to the environment. In this article, the results of tests conducted on vibrations of elements of the analyzed structure are presented, and the level of these vibrations in terms of meeting the requirements of the European standards is assessed. Vibrating criteria of structure performance were checked, and safety was assessed. The results of noise measurements in the vicinity of the analyzed bridge are also presented, and the environmental impact of this structure is determined. The test results show that the bridge meets the requirements for vibration acceleration and noise. An increased acoustic emission in the analyzed case does not pose a significant threat, but if this type of structure was on high supports in an urbanized area, it would be a nuisance to the environment.